STATISTICAL STUDY OF ACCOUNTING REPORTS IN MANUFACTURING ENTERPRISES (Academia Science Repository, 2023)
In the current economic conditions, the activity of each business entity is the focus of an extensive range of market participants interested in the results of its functioning. In this regard, the importance of reliable and objective of financial statements is increasing dramatically, for the analysis of its parameters allows to determine the true financial position of the enterprise. Reporting one of the main methods of accounting methodology and statistics.